1984
DOI: 10.1136/vr.115.23.599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding on the fate of orally administered phenylbutazone, trimethoprim and sulphadiazine in the horse

Abstract: Phenylbutazone, sulphadiazine and trimethoprim were administered to three horses on two occasions, recently fed and unfed, and the effect of feeding on the pharmacokinetics of the three drugs assessed. The mean peak concentrations of phenylbutazone and trimethoprim were reduced by feeding by 34 and 75 per cent, respectively. The pharmacokinetics of sulphadiazine were not significantly affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…A possible interpretation is that ivermectin remains adsorbed to the particulate phase of the digesta during intestinal transit, and thus is not available anymore for absorption in the intestinal fluids. Such a situation has already been described for other compounds such as phenylbutazone [5,16] and is consistent with the high organic-carbon binding constant of ivermectin (K oc = 12600-15700; [11]) and its high hydrophobicity [20]. Ivermectin oral bioavailability was estimated from the model to be 28 ± 13.2%, which is in line with the bioavailability found by Chiu et al [8] in cattle for an intraruminal bolus of ivermectin relative to the subcutaneous route (26%).…”
Section: Discussionmentioning
confidence: 54%
“…A possible interpretation is that ivermectin remains adsorbed to the particulate phase of the digesta during intestinal transit, and thus is not available anymore for absorption in the intestinal fluids. Such a situation has already been described for other compounds such as phenylbutazone [5,16] and is consistent with the high organic-carbon binding constant of ivermectin (K oc = 12600-15700; [11]) and its high hydrophobicity [20]. Ivermectin oral bioavailability was estimated from the model to be 28 ± 13.2%, which is in line with the bioavailability found by Chiu et al [8] in cattle for an intraruminal bolus of ivermectin relative to the subcutaneous route (26%).…”
Section: Discussionmentioning
confidence: 54%
“…T h e fact that the horses were fed shortly after dosing may have influenced unduly the uptake of ivermectin. Adsorption of drug to ingesta has been shown to alter the pharmacokinetics of various drugs (Lees et al, 1983;Bogan et al, 1984) although it might be expected that, if this was the case, adsorption to abomasal content should also occur at least to some degree. Lo et al (1985) have reported on extensive investigations on the effect of formulation on the pharmacokinetics of ivermectin in cattle, sheep and pigs.…”
Section: Horse Experimentsmentioning
confidence: 99%
“…80 Interestingly, these experimental horses were allowed free access to prairie hay, potentially reducing the bioavailability of the drug. 79 Additionally, because PYR is concentrated in CNS tissue relative to plasma, 81 the concentration at the desired site of action may be greater than 0.1 mg/mL. Mean peak CSF concentrations of sulfonamide after single or multiple dosing (22-44 mg/kg) are reported to be approximately 2 to 8 mg/mL.…”
Section: Folate-inhibiting Drugsmentioning
confidence: 98%